97.1k views
4 votes
Simplify: (sin Θ − cos Θ)^2 + (sin Θ + cos Θ)^2

2 Answers

7 votes
hope this could help you
Simplify: (sin Θ − cos Θ)^2 + (sin Θ + cos Θ)^2-example-1
User Jashira
by
5.5k points
2 votes

Answer: The required simplified value of the given expression is 2.

Step-by-step explanation: We are given to simplify the following trigonometric expression :


T_E=(\sin\theta-\cos\theta)^2+(\sin\theta+\cos\theta)^2~~~~~~~~~~~~~~~~~~~~~~~~~(i)

We will be using the following formulas :


(i)~(a-b)^2=a^2-2ab+b^2,\\\\(ii)~(a+b)^2=a^2+2ab+b^2,\\\\(iii)~\sin^2\theta+\cos^2\theta=1.

From (i), we have


T_E\\\\=(\sin\theta-\cos\theta)^2+(\sin\theta+\cos\theta)^2\\\\=\sin^2\theta-2\sin\theta\cos\theta+\cos^2\theta+\sin^2\theta+2\sin\theta\cos\theta+\cos^2\theta\\\\=2(\sin^2\theta+\cos^2\theta)\\\\=2*1\\\\=2.

Thus, the required simplified value of the given expression is 2.

User Smamatti
by
5.5k points